Everyday mathematics and the standards for mathematical practice (Mc Graw Hill, 2012)
The Common Core State Standards for Mathematics (CCSS-M) includes both Content Standards and Standards for Mathematical Practice. The Content Standards specify skills and understandings that students should develop at each grade, whereas the Standards for Mathematical Practice identify processes and proficiencies that students should develop throughout their mathematical education at all levels.